Transformational Leadership and Community Peace building-Security Leadership as a Model - a Field Study in the City of Baghdad (Journal Of Educational and Psychological Researches, 2024)
Leadership is a vital element for the success of institutions in achieving their goals, including security institutions that are responsible for providing security and internal peace for individuals in society, which depends on the applied leadership style. The research problem crystallizes in the nature and size of the challenges facing societal peace and what the network of social relations is exposed to in light of the state of political and institutional instability. The study aims to evaluate the security environment, the possibility of activating the role of security leaders in promoting community peace building and studying ways and mechanisms to achieve it, and the extent of the impact of transformational leadership in building societal peace as a modern leadership style and method. The security institutions (Ministry of Defense, Ministry of Interior, and National Security Service) were chosen as a population for the study. 200 managers, leaders, and experts were chosen as the research sample. A questionnaire was adopted as a tool for collecting data, which was designed, judged, and analyzed for validity, reliability, and analysis based on SPSS Ver.24